PENGARUH AEROSOL TERHADAP FLUKS RADIASI NETO DI LAPISAN ATAS ATMOSFER DAN DI PERMUKAAN BERDASAR DATA SATELIT [INFLUENCE OF AEROSOL ON NET RADIATION FLUX AT THE TOP OF ATMOSPHERE AND SURFACE BASED ON SATELLITE] - nFN Rosida; Indah Susanti (Jurnal Sains Dirgantara, 2016)
The direct effects of aerosols on radiation budget in Indonesia have been analyzed based on radiation flux net data from the Clouds and the Earth's Radiant Energy System (CERES) instrument and aerosol optical depth (AOD) from the Moderate Resolution Imaging Spectroradiometer (MODIS) Terra. Radiation budget calculated including short wave and long-wave radiation. Data from March 2000 until February 2010, processed using Grads version 2 to obtain aerosol radiative forcing value. Net radiation in clean sky, estimated using slope method. The analysis showed high temporal variation of aerosols density in the atmosphere with a value AODmax> 2, which generally causes decreases net radiation flux, so providing a cooling effect. The influence of aerosols on the net radiation flux can be very clearly seen in the case of forest fires. AOD in 2006 increased and caused radiation flux anomalies ranging from -9 watt/m-2 to -14 watts/m-2, with the largest decline occurred in the surface. From all the data period, aerosol radiative forcing at TOA level (ARFTOA) on Indonesia was -0.49 watt/m-2 and aerosol radiative forcing at the surface level (ARFSurf) on Indonesia was -17.72 watt/m-2, that influence to the Indonesian climate condition.